Rozwiąż równanie i nierówność:
a) (x+5) do potęgi 2 = ( 4-x) do potęgi 2
b) (3+x)(3-x) > ( pod tym znakiem gdzie ta strzałka to jest jeszcze kreska) x(5-x)-1


Odpowiedź :

Cześć!

a)

[tex](x+5)^2=(4-x)^2\\\\x^2+2\cdot x\cdot5+5^2=4^2-2\cdot4\cdot x+x^2\\\\x^2+10x+25=16-8x+x^2\\\\x^2+10x+8x-x^2=16-25\\\\18x=-9 \ \ /:18\\\\\boxed{x=-\frac{1}{2}}[/tex]

b)

[tex](3+x)(3-x)\geq x(5-x)-1\\\\3^2-x^2\geq5x-x^2-1\\\\9-x^2\geq5x-x^2-1\\\\-x^2-5x+x^2\geq-1-9\\\\-5x\geq-10 \ \ /:(-5)\\\\x\leq2\\\\\boxed{x\in(-\infty;2\rangle}[/tex]